Identification and transcriptome analysis of erythroblastic island macrophages - Li, Wei; Wang, Yaomei; Zhao, Huizhi; Zhang, Huan; Xu, Yuanlin; Wang, Shihui; Guo, Xinhua; Huang, Yumin; Zhang, Shijie; Han, Yongshuai; Wu, Xianfang; Rice, Charles M.; et al. (Blood, 2019)
The erythroblastic island (EBI), composed of a central macrophage and surrounding erythroid cells, was the first hematopoietic niche discovered. The identity of EBI macrophages has thus far remained elusive. Given that Epo is essential for erythropoiesis and that Epor is expressed in numerous nonerythroid cells, we hypothesized that EBI macrophages express Epor so that Epo can act on both erythroid cells and EBI macrophages simultaneously to ensure efficient erythropoiesis. To test this notion, we used Epor-eGFPcre knockin mouse model. We show that in bone marrow (BM) and fetal liver, a subset of macrophages express Epor-eGFP. Imaging flow cytometry analyses revealed that >90% of native EBIs comprised F4/80+Epor-eGFP+ macrophages. Human fetal liver EBIs also comprised EPOR+ macrophages. Gene expression profiles of BM F4/80+Epor-eGFP+ macrophages suggest a specialized function in supporting erythropoiesis. Molecules known to be important for EBI macrophage function such as Vcam1, CD169, Mertk, and Dnase2α were highly expressed in F4/80+Epor-eGFP+ macrophages compared with F4/80+Epor-eGFP− macrophages. Key molecules involved in iron recycling were also highly expressed in BM F4/80+Epor-eGFP+ macrophages, suggesting that EBI macrophages may provide an iron source for erythropoiesis within this niche. Thus, we have characterized EBI macrophages in mouse and man. Our findings provide important resources for future studies of EBI macrophage function during normal as well as disordered erythropoiesis in hematologic diseases such as thalassemia, polycythemia vera, and myelodysplastic syndromes. •EBI macrophages are characterized by the expression of Epor in mouse and man.•Transcriptomes data provide resource for future studies of EBI macrophage function in normal and disordered erythropoiesis. [Display omitted]